PZT components derived from polysulphone spinning process. (12th May 2015) - Hohlfeld, K.; Gebhardt, S.; Schönecker, A.; Michaelis, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The present paper deals with the development of lead zirconate titanate (PZT) fibres, pearls and fibre fragments, for their use as active phase in piezocomposites. As new a approach, the green ceramic components are shaped by polysulphone spinning, allowing for effective and flexible forming over a wide range of different geometries and sizes.1 The correlation between processing parameters, e.g. the slurry composition, nozzle size and operation velocity, and the resultant shape of ceramic components is analysed. Sintered piezoceramic parts show a dense microstructure. Performance data are evaluated on PZT/epoxy composites. Measurement results of strain, polarisation and piezoelectric coupling are given and discussed. The developed PZT components are seen as key for the creation of smart and lightweight structural components. Further, free formed PZT components open new design approaches for sensing and actuating devices and ultrasound transducers.